An Itinerary - Moryson, Fynes, 1566-1630. (Glasgow Glasgow)
4 cilt (1. c. xxv, 467, [1] sayfa, [7] sayfa resim ; 2. c. [3], 465, [1] sayfa, [5] sayfa resim ; 3. c. vi, 498, [1] sayfa, [5] sayfa resim ; 4. c. ix, 520, [1] sayfa)